Determining the fireproof limit for the heat protective coating of the gas generator in a hydrogen storage and supply system - Abramov, Yuriy; Basmanov, Oleksii; Krivtsova, Valentina; Mikhayluk, Andriy; Makarov, Yevhen; Abrakitov, Volodymyr (Eastern-European journal of enterprise technologies, 2025)
This work considers the task to prevent fires in hydrogen storage and operation systems. The subject of the study is the properties of the heat-protective coating of the gas generator in the hydrogen storage and supply system. The fire resistance limit is used as such a property. The set of heat-protective coating and the wall of the gas generator is considered as a thermodynamic system with two inputs. The signal at one input reflects the influence of thermal factors of the fire, and the signal at the second input corresponds to the thermal state of the gas generator cavity. A mathematical description of such a thermodynamic system has been constructed, which is represented in operator form using the integral Laplace transform. A feature of such a mathematical notation is that it includes hyperbolic functions of an irrational argument. An approximation of mathematical models of the thermodynamic system was carried out and it is shown that these models, which are transfer functions, belong to fractional-rational functions with third-order Hurwitz polynomials. The approximation accuracy is 3.8%. An expression for the reaction of a thermodynamic system has been derived, provided that the influence of thermal factors of a fire is described by an arbitrary function of time, and the thermal state of the gas generator cavity is described by the Heaviside function. To construct this expression, the Borel theorem and auxiliary functions are used, the parameters of which are the parameters of the roots of the algebraic Hurwitz equation. Examples of determining the fire resistance limit for the heat-protective coating of the gas generator in the hydrogen storage and supply system for the characteristic conditions of its operation are given. It is shown that the fire resistance limit of such a coating is 462.8 s at a critical temperature of 320°C under the condition that the influence of thermal factors of a fire is linear (the generalized temperature change rate is 2.0°C s-1). In this case, the thermal state of the gas generator cavity is stationary and is characterized by a temperature of 60°C Роботу присвячено проблемі запобігання пожеж в системах зберігання і експлуатації водню. Предметом дослідження є властивості теплозахисного покриття газогенератора системи зберігання та подачі водню. В якості такої властивості використовується межа вогнестійкості. Сукупність теплозахисного покриття і стінки газогенератора розглядається як термодинамічна система, яка має два входи. Сигнал на одному вході відображає вплив теплових чинників пожежі, а сигнал на другому вході відповідає тепловому стану порожнини газогенератора. Побудовано математичний опис такої термодинамічної системи, який представлено в операторній формі із використанням інтегрального перетворення Лапласа. Особливістю такого математичного опису є те, що він включає гіперболічні функції ірраціонального аргументу. Здійснено апроксимацію математичних моделей термодинамічної системи і показано, що ці моделі, які є передаточними функціями, належать до дробово-раціональних функцій із поліномами Гурвіца третього порядку. Точність апроксимації складає 3,8%. Одержано вираз для реакції термодинамічної системи за умови, що вплив теплових чинників пожежі описується довільною функцією часу, а тепловий стан порожнини газогенератора описується функцією Хевісайда. Для побудови цього виразу використовується теорема Бореля та допоміжні функції, параметрами яких є параметри коренів алгебраїчного рівняння Гурвіца. Наведено приклади визначення межі вогнестійкості теплозахисного покриття газогенератора системи зберігання та подачі водню для характерних умов її експлуатації. Показано, що межа вогнестійкості такого покриття складає 462,8 с при критичній температурі 320°С за умов, що вплив теплових чинників пожежі має лінійний характер (узагальнена швидкість зміни температури складає 2,0°С·с-1). При цьому тепловий стан порожнини газогенератора є стаціонарним і характеризується температурою 60°C